(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe clinical features of dermatophytosis at Can Tho University of Medicine and Pharmacy Hospital. Subjects and methods: Cross-sectional descriptive study of 100 patients with dermatophytosis at Can Tho University of Medicine and Pharmacy Hospital. Results: A study of 100 patients with dermatophytosis at Can Tho University of Medicine and Pharmacy Hospital found that common lesions are erythema 96%, macules 88%, well demarcated 80%; common lesions locations are the abdomen and upper limbs with the same rate of 23%; the back and lower limbs with the rates of 21% and 20%, respectively. The number of lesions from 2 - 5 is the most, accounting for 43%, the area of lesion ≤ 1 hand is the most common, accounting for 53%, the severity of the disease is mostly moderate and severe, respectively 40% and 39%. The clinical presentation of tinea corporis are predominated. The duration of the disease was less than 3 months (51%). Conclusions: In this study, common clinical features of dermatophytosis include erythematous lesions, well demarcated, continuous-edged macules, with 2-5 lesions, ranging from moderate to severe, the most common form being tinea corporis, and a disease duration usually less than 3 months.